The small heat shock protein αB-Crystallin protects versus withaferin A-induced apoptosis and confers a more metastatic phenotype in cisplatin-resistant ovarian cancer cells. - Melissa M Carmichael; Israa Alchaar; Kathleen A Davis; Merideth Kamradt Krevosky (PLoS ONE)
Since a majority of ovarian tumors recur in a drug-resistant form leaving patients few treatment options, the goal of this study was to explore phenotypic and molecular characteristics of a cisplatin-resistant ovarian cancer cell line (OVCAR8R) as compared to its cisplatin-sensitive syngeneic counterpart (OVCAR8) and to explore the effectiveness of a novel chemotherapeutic, Withaferin A (WA). In addition to unique morphological characteristics, the small heat shock proteins (Hsps) αB-Crystallin (HspB5) and Hsp27 are constitutively expressed along with increased expression of vimentin in OVCAR8R cells, while OVCAR8 cells do not endogenously express these Hsps, supporting that Hsp overexpression may confer resistance to chemotherapy and promote more aggressive tumor types. WA increases apoptosis in a dose-dependent manner in OVCAR8 cells, while OVCAR8R cells remain more viable at comparable doses of WA coincident with the upregulation of αB-Crystallin. To determine the significance of αB-Crystallin in conferring a more aggressive phenotype, αB-Crystallin was silenced by CRISPR-Cas9 in OVCAR8R cells. The morphology of the OVCAR8R clones in which αB-Crystallin was silenced reverted to the morphology of the original cisplatin-sensitive OVCAR8 cells. Further, cisplatin-resistant OVCAR8R cells constitutively express higher levels of vimentin and migrate more readily than cisplatin-sensitive OVCAR8 and OVCAR8R cells in which αB-Crystallin was silenced. Transient overexpression of wildtype αB-Crystallin, but not a chaperone-defective-mutant, alters the morphology of these cells to closely resemble the cisplatin-resistant OVCAR8R cells and protects versus WA-induced apoptosis. Together, this research supports the potential effectiveness of WA as a therapy for ovarian cancer cells that have not yet acquired resistance to platinum-based therapies, and importantly, underscores that αB-Crystallin contributes to a more aggressive cellular phenotype and as such, may be a promising molecular target for a better clinical outcome.